2003
DOI: 10.1093/ps/82.6.939
|View full text |Cite
|
Sign up to set email alerts
|

Systems-wide chicken DNA microarrays, gene expression profiling, and discovery of functional genes

Abstract: The goal of our current consortium project is to launch a new era--functional genomics of poultry--by providing genomic resources [expressed sequence tags (EST) and DNA microarrays] and by examining global gene expression in target tissues of chickens. DNA microarray analysis has been a fruitful strategy for the identification of functional genes in several model organisms (i.e., human, rodents, fruit fly, etc.). We have constructed and normalized five tissue-specific or multiple-tissue chicken cDNA libraries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 54 publications
2
88
0
2
Order By: Relevance
“…Probing balanced selection and breeding for growth, reproduction, immunity, and metabolism in chickens for optimum performance has become a hot topic in research (Ou et al, 2009). The candidate gene approach is becoming increasingly economical and effective for finding candidate genes and quantitative trait nucleotides with significant effects on economically important traits (Kanehisa et al, 2002;Cogburn et al, 2003;Zhu and Zhao, 2007;Kuhn et al, 2008). According to the integration strategies described above, the PRLR gene was effectively selected and used to study genetic associations with egg production traits.…”
Section: Discussionmentioning
confidence: 99%
“…Probing balanced selection and breeding for growth, reproduction, immunity, and metabolism in chickens for optimum performance has become a hot topic in research (Ou et al, 2009). The candidate gene approach is becoming increasingly economical and effective for finding candidate genes and quantitative trait nucleotides with significant effects on economically important traits (Kanehisa et al, 2002;Cogburn et al, 2003;Zhu and Zhao, 2007;Kuhn et al, 2008). According to the integration strategies described above, the PRLR gene was effectively selected and used to study genetic associations with egg production traits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adipose tissue gene expression arrays have failed to detect leptin in lean or fat strains of broilers . Similarly, extensive microarray analysis of chicken fat, liver, and other tissues has failed to identify leptin (Cogburn et al 2004, as has extensive EST screening of fat and other tissues (Cogburn et al 2003, Carre et al 2006 and proteomic analysis of abdominal adipose tissues of fat and lean broilers .…”
Section: Discussionmentioning
confidence: 99%
“…However, the CLEPR ligand has not yet been found (Friedman-Einat et al 1999, Dunn et al 2001, Amills et al 2003, Sharp et al 2008, Pitel et al 2009). In addition, despite the nearly complete sequencing of the chicken genome (Burt 2006) and extensive sequencing of chicken fat expressed sequence tags (ESTs) (Cogburn et al 2003), no sequence similarity to leptin has been identified, nor has any similarity been found at the protein level (Sharp et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these studies have provided information on global gene expression in chickens. Microarray analysis has proven useful as a flourishing approach for the classification of functional genes in several model organisms (e.g., humans, rodents, and fruit flies) (Cogburn et al, 2003) and is considered as a powerful tool for visualizing the molecular mechanism that governs complex biological responses; it is also used in gene expression analysis (van Hal et al, 2000). The technology is primarily used to assess the expression of different genes, search for new genes, the molecular diagnosis of disease, gene mutation and polymorphism analyses, and drug development in order to analyze and ascertain the specificity of these comprehensive gene expressions on large scale (Nakachi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%